2014
DOI: 10.3390/ijerph110808267
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Exposure to Drugs of Abuse by Hair Testing: Monitoring 15 Years of Evolution in Spain

Abstract: Hair testing is a useful tool to investigate the prevalence of unsuspected chronic exposure to drugs of abuse in pediatric populations and it has been applied to three different cohorts of children from Barcelona, Spain along fifteen years to evaluate eventual changes in this exposure. Children were recruited from three independent studies performed at Hospital del Mar (Barcelona, Spain) and approved by the local Ethics Committee. Hair samples were collected from the first 187 children cohort (around 4 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…Hair has become a popular matrix for forensic toxicological purposes, such as abstinence controls, for example driving license regranting procedures, workplace drug testing, and child custody cases . Hair testing has many benefits for both the examiner and the examinee.…”
Section: Introductionmentioning
confidence: 99%
“…Hair has become a popular matrix for forensic toxicological purposes, such as abstinence controls, for example driving license regranting procedures, workplace drug testing, and child custody cases . Hair testing has many benefits for both the examiner and the examinee.…”
Section: Introductionmentioning
confidence: 99%
“…The results of several study cohorts demonstrated a significant prevalence of unsuspected pediatric exposure to drugs of abuse, which mainly involved cocaine, for example, in Barcelona, Spain [30]. The results of several study cohorts demonstrated a significant prevalence of unsuspected pediatric exposure to drugs of abuse, which mainly involved cocaine, for example, in Barcelona, Spain [30].…”
Section: Discussionmentioning
confidence: 93%
“…Pasif maruziyet açısından bebekler ve küçük çocuklar daha çok ev içinde vakit geçirdikleri için daha büyük çocuklara göre daha fazla risk altındadırlar. Özellikle sigara şeklinde kullanım sonrası ortaya çıkan dumanı solumak veya ortamda bulunan kontamine olmuş maddelerle temas pasif maruziyet durumu oluşturabilmektedir (47). Ayrıca gebelerde plasenta üzerinden, emzirme veya kullanıcının tükürüğü veya teri yoluyla pasif olarak çocuklar maddelere maruz kalabilmektedirler.…”
Section: şEkil 2 Suistimal Edilebilen Maddelerin Analizinde Kullanıla...unclassified